1996
DOI: 10.1164/ajrccm.153.2.8564115
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant treatment before reperfusion improves the immediate function of lung transplants in rats.

Abstract: An impaired function of alveolar surfactant can cause lung transplant dysfunction early after reperfusion. In this study it was investigated whether treatment with surfactant before reperfusion improves the immediate function of lung transplants and whether an improved transplant function was associated with an increase in alveolar surfactant components. Left lungs with 6-h (n = 8) or prolonged 20-h ischemia (n = 10) were transplanted syngeneically in rats. In both ischemia groups half of the lung transplants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 49 publications
3
49
2
Order By: Relevance
“…Several studies have identified the important role of surfactant alterations in transplantationrelated I/R injury of the lung [8,9,[35][36][37][38][39][40]. Accordingly, exogenous surfactant therapy has been applied successfully in experimental [12][13][14][15][16][17][18][19][20][21] and clinical [22][23][24] studies. It is, therefore, considered a potentially promising therapy for the mitigation of severe lung I/R injury, although the optimal surfactant preparation and mode of therapy still need to be determined [26,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified the important role of surfactant alterations in transplantationrelated I/R injury of the lung [8,9,[35][36][37][38][39][40]. Accordingly, exogenous surfactant therapy has been applied successfully in experimental [12][13][14][15][16][17][18][19][20][21] and clinical [22][23][24] studies. It is, therefore, considered a potentially promising therapy for the mitigation of severe lung I/R injury, although the optimal surfactant preparation and mode of therapy still need to be determined [26,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental [12][13][14][15][16][17][18][19][20][21] and clinical [22][23][24] studies give evidence that exogenous surfactant therapy successfully supplements the imbalanced endogenous surfactant system, serving to attenuate I/R injury and effectively improve lung preservation and graft function [11]. The great advantage of exogenous surfactant therapy of the donor in human lung transplantation is the fact that PGD in this case can accurately be predicted and, thus, even be prevented, providing a promising approach for prophylactic surfactant therapy [11,25,26].…”
mentioning
confidence: 99%
“…L -1 K + ) group was associated with superior ultrastructural preservation of tubular myelin. The percentage of the large aggregate subfraction in bronchoalveolar lavage studies represents a parameter that has been used as an indicator of surfactant function in acute lung injury [4,9,14,30]. Based on the current observations, the authors propose that the fraction of surface active tubular myelin, which largely corresponds to the bronchoalveolar lavage large aggregate subfraction [4], represents an important criterion for the assessment of the structural integrity of intraalveolar surfactant in studies investigating lung preservation quality.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1966, experimental data generated in lung transplantation models have provided evidence for surfactant abnormalities and depletion after lung ischemia-reperfusion injury (LIRI) [1][2][3][4][5][6]. In 1998, Hohlfeld and colleagues demonstrated surfactant alterations in human lung transplant recipients, more than 1 year after transplantation [7].…”
Section: Introductionmentioning
confidence: 99%